The antioxidant, anti-cholangiocarcinoma, and anti-Opisthorchis viverrini activities of ethanolic extract from Antidesma thwaitesianum fruit. (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: The current study was performed to determine the antioxidant, anti-inflammatory, and anti-cholangiocarcinoma (CCA) properties of Antidesma thwaitesianum, also known as “MAO,” whole plant extract on Opisthorchiasis in animal models and CCA cell lines. Materials and Methods: Ethanol was used to extract compounds from the whole ripe fruit. The phytochemical investigation of MAO extract was done to evaluate antioxidant activity, and high-performance liquid chromatography was used to identify the active compounds. The efficacy of MAO extract against OV was evaluated in vivo. The anti- CCA activity was evaluated using superoxide dismutase (SRB), cell cycle arrest, apoptosis, and western blot analyses. Results: MAO extract possessed flavonoid and phenolic contents, antioxidant activity, and an expressed cyanidin-3-O-glycosides content of 0.08 µg/mg extract. MAO extract demonstrated hepatoprotective effects through raised alanine transaminase and alkaline phosphatase levels, as well as an influence on oxidative stress via decreased MDA and increased glutathione, superoxide dismutase, and catalase levels. MAO extract significantly inhibited the migration of CCA cells in a concentration- and time-dependent manner, as well as triggered cell cycle arrest on G1 and activated apoptosis pathways via upregulation of C3, downregulation of cyclin-dependent kinase inhibitor p21, cyclin D, and cyclin-dependent kinases 2 expression. MAO extract inhibited inflammation, which in turn decreased fibrosis in hamsters. It also increased hepatoprotective activity. Conclusion: Our findings demonstrate the potential benefits of MAO extract in both in vitro and animal studies of hamster opisthorchiasis. However, more research should be done to ascertain the mechanisms of activity of MAO extracts and elute bioactive components in order to confirm their safety and examine their clinical applications.J. Adv. Vet. Anim. Res., 11(3): 637–647, September 2024http://doi.org/10.5455/javar.2024.k813